Artificial Intelligence as a Subject of a Crime - Andrey BAYBARIN; Alexander GREBENKOV; Anton BAUMSTEIN; Maria SINYAEVA (Communications of International Proceedings, 2020)
The article examines the legal responsibility of artificial intelligence, identifies problematic aspects, suggests ways to solve them. It is concluded that it is impossible to talk about the possibility of recognizing its full legal personality. In our opinion, the legislator should not go along the path of creating the possibility of bringing artificial intelligence systems to justice, but on the path of ensuring more detailed control over the actions of their developers and operators, and the development of appropriate standards.
Keywords: Artificial Intelligence; Crime; Responsibility; System; Intellectual Activity.